Organizational learning in hospitals: A realist review. (10th July 2019) - Lyman, Bret; Jacobs, Jonathan D.; Hammond, Emily L.; Gunn, Margaret M.
Abstract: Aim: To establish a middle‐range theory of organizational learning in hospitals. Design: A realist review of the literature, conducted according to established standards for realist and meta‐narrative evidence syntheses. Middle‐range theory development was performed according to Smith and Liehr's recommendations. Data sources: Two comprehensive scientific databases and six discipline‐focused databases spanning health care, life sciences, business, sociology, and psychology were searched from inception to 12 May 2016. Review methods: Citations meeting the inclusion criteria were appraised using the Mixed Methods Appraisal Tool. Data extraction was guided by a focus on the contextual factors, mechanisms, and outcomes associated with organizational learning. Results: The initial search yielded 2, 332 citations, 147 of which were ultimately included in the review. The included citations were generally of high quality. Reviewed evidence indicates certain aspects of organizational context can be conducive to mechanisms of organizational learning, leading to a range of positive organizational outcomes. Conclusion: This review updates and expands on a previous review of the literature on organizational learning in hospitals, refines the concept of organizational learning in hospitals, and provides a middle‐range theory of organizational learning in hospitals. Impact: This updated review provides a strong evidence base for future work on the topic of organizational learning in hospitals. The refined concept of organizational learning makes it possible to develop reliable, valid research instruments that better reflect of the full scope of organizational learning. Finally, the middle‐range theory guides researchers and clinical leaders as they advance the science and practice of organizational learning. Abstract : 目的: 在于确立医院机构内学习的中层理论。 设计: 根据现实主义和元叙事证据合成的既定标准对文献进行现实主义综述。中层理论的发展是根据Smith 和Liehr的建议进行的。 资料来源: 从收录到2016年5月12日, 搜索了两大综合科学数据库和六大以学科为中心的数据库, 涵盖了医疗保健、生命科学、商业、社会学和心理学。 综述方法: 使用了混合方法型评估工具来评估符合入选标准的引文。数据提取以关注与机构内学习相关的背景因素、机制和结果为指导。 结果: 初始搜索产生了2332个引文, 其中147个最终被纳入综述。收录的引文质量一般都很高。经过审查的证据表明, 机构背景的某些方面有利于机构内学习机制, 从而产生一系列积极的机构绩效。 结论: 本综述更新和扩展了以往关于医院机构内学习的文献, 提炼了医院机构内学习的理念, 并提供了医院机构内学习的中层理论。 影响: 这一最新综述为医院机构内学习这一主题的未来工作提供了强有力的证据基础。机构内学习的精细理念使得开发可靠且有效的研究工具成为可能, 这些工具能够更好地反映机构内学习的全部范围。最后, 中层理论指导研究人员和临床负责人推进机构内学习的科学和实践。